2017
DOI: 10.1111/evo.13255
|View full text |Cite
|
Sign up to set email alerts
|

Is a larger refuge always better? Dispersal and dose in pesticide resistance evolution

Abstract: The evolution of resistance against pesticides is an important problem of modern agriculture. The high‐dose/refuge strategy, which divides the landscape into treated and nontreated (refuge) patches, has proven effective at delaying resistance evolution. However, theoretical understanding is still incomplete, especially for combinations of limited dispersal and partially recessive resistance. We reformulate a two‐patch model based on the Comins model and derive a simple quadratic approximation to analyze the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…For example, a spatially explicit model may be required when dispersal distances must be considered, or a stochastic model may be necessary to evaluate the effects of finite population size. In addition for specific cases, particular dispersal (0 < d x < 1) and refuge values (k ≠ 0.5) should be examined, as the waiting time to resistance is a nonlinear function of these parameters (Takahashi, Yamanaka, Sudo, & Andow, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a spatially explicit model may be required when dispersal distances must be considered, or a stochastic model may be necessary to evaluate the effects of finite population size. In addition for specific cases, particular dispersal (0 < d x < 1) and refuge values (k ≠ 0.5) should be examined, as the waiting time to resistance is a nonlinear function of these parameters (Takahashi, Yamanaka, Sudo, & Andow, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In part, this leads to indecision and the prophylactic application of insecticides potentially increasing the risk of resistance. The risk is dependent on numerous factors such as the genetic basis of resistance across field doses, the starting resistance allele frequencies and pest dispersal rates . Thresholds help to rationalize the use of insecticides and are a fundamental tenet underpinning IPM practices, assuming they are accurate and appropriately applied.…”
Section: The Future Of Resistance Management In Australian Grainsmentioning
confidence: 99%
“…The risk is dependent on numerous factors such as the genetic basis of resistance across field doses, the starting resistance allele frequencies and pest dispersal rates. 56 Thresholds help to rationalize the use of insecticides and are a fundamental tenet underpinning IPM practices, 57 assuming they are accurate and appropriately applied. A recent review commissioned by the GRDC identified numerous gaps in economic thresholds available within the Australian grain industry (Miles M, personal communication).…”
Section: Greater Adoption Of Ipmmentioning
confidence: 99%
“…The second approach, selectively applying treatment, involves targeting treatments to particular pests, and providing specific remedies long enough and in high enough concentrations to eliminate the pest populations entirely (Takahashi et al., 2017, transgenic crops and susceptible arthropods). A variant of this approach includes integrated pest management, in which locally variable application of treatments creates a spatially heterogeneous environment of selection intensities, designed to slow the rate at which resistance evolves (Tabashnik et al., 2003, 2008; lepidopterous insects).…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for generating sterile males include ionizing radiation (reviews in VanDyck et al., 2005; Balestrino et al., 2017), conditional-lethal genotypes (Ant et al., 2012), and CRISPR-cas9 applications (Borel, 2017; Drury et al., 2017). Additional detail on the approaches described above are available elsewhere (Palumbi, 2001; Tabashnik et al., 2008; Frieri et al., 2016; Takahashi et al., 2017; Harris, 2017; Borel, 2017).…”
Section: Introductionmentioning
confidence: 99%